HISTORICAL RISK ANALYSIS OF HEART DISEASE IN SULSEL EXPO PARTICIPANTS - Yudi Adnan; Nildawati Nildawati; Andi Awaliyah Latif (Universitas Islam Negeri Alauddin Makassar, 2020)
Background: Currently PTM has become the biggest cause of deathin the world. As many as 38 million (68%) of the 56 million deaths in the world in 2012 were caused by PTM. Coronary heart disease is one of the non-communicable diseases with the largest mortality rate.Objective: This study aims to analyze the factors associated with a history of heart disease in the participants of the South Sulawesi Expo 2018.Method: The type of research used is quantitative analytic with a cross-sectional approach.Sampling using purposive sampling technique so that the number of samples is 107 peopleResult: There is a significant relationship between a history of diabetes, hypertension, heart disease, stroke, and cancer in the family against a history of heart disease (p <0.05) in the 2018 South Sulawesi Expo participants, while there is no significant relationship between the history of asthma and cholesterol. smoking behavior, consumption of fruits and vegetables, physical activity, and alcohol consumption (p> 0.05) on the history of heart disease among participants in South Sulawesi Expo 2018.Conclusion: Government involvement is needed to provide education for the community related to the prevention of PTM, and for the community to continue to strive to improve patterns of life to avoid PTM.